Direct vector controlled six-phase asymmetrical induction motor with power balanced space vector PWM multilevel operation. (2016) - Sanjeevikumar, Padmanaban; Grandi, Gabriele; Ojo, Joseph Olorunfemi; Blaabjerg, Frede
In this paper, a six-phase (asymmetrical) machine is investigated, 300 phase displacement is set between two three-phase stator windings keeping deliberately in open-end configuration. Power supply consists of four classical three-phase voltage inverters (VSIs), each one connected to the open-winding terminals. An original synchronous field oriented control (FOC) algorithm with three variables as degree of freedom is proposed, allowing power sharing among the four VSIs in symmetric/asymmetric conditions. A standard three-level space vector pulse width modulation (SVPWM) by nearest three vector (NTV) approach was adopted for each couple of VSIs to operate as multilevel output voltage generators. The proposed power sharing algorithm is verified for the ac drive system by observing the dynamic behaviours in different set conditions by complete simulation modelling in software (Matlab/Simulink-PLECS) and the results are provided in this paper. Furthermore, harmonic components are shown in each subspace and analysed with Fourier spectrum to confirm the smooth torque propagation with free of harmonic components. The numerical simulation results provided in this paper are closely matching with theoretical developments.